They Say That the World Was Built for Two, But Deceptive Patterns Say Otherwise: A Critical Game for Player Empowerment - Santos Filho, Luiz; Sousa Junior, Alairton; Ribeiro, Giovanna; Darin, Ticianne (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
The digital games industry constantly grows, earning billions of dollars annually. However, developers often use design patterns detrimental to the player’s well-being to profit and engage players. These practices are called “Deceptive Patterns”. The frequency of use of these patterns frustrates players’ basic psychological needs, leading to ill-being and undesirable outcomes, such as addictive behavior. Although there is already knowledge about these negative patterns, oftenly players continue to be impacted by these practices, unware of their damages. To promote discussion on this topic, we developed a critical game based on Self-Determination Theory (SDT) concepts to stimulate critical reflection on the use and consequences of using these patterns in games. We evaluated the game’s interest in players about the theme and the quality of the game-player interaction, considering playability, player experience, and engagement. For that, we employed the Playability Model, Player Experience Brazilian Inventory (PX-Br), and User Engagement Scale in Portuguese (UES-Br). The results shows that although users recognize some of these patterns, they are unaware of the negative impact that deceptive patterns can have on players. In addition, the results indicate positive playability, especially the interactive aspect. The player experience and engagement were also evaluated positively, with emphasis on constructs such as fun, playability and aesthetic appeal.